Tersejahteranya Guru Honorer dengan Adanya Kebijakan P3K - Utami, Sherin Dwi; Utami, Lutfi Wahyu; Setiawan, Farid; Lestari, Salsa Warda (Lembaga Yasin AlSys, 2023)
In the current era, many young people are less interested in having aspirations to become teachers, even though being a teacher is a very noble profession, so the purpose of this research is to examine what factors make young people who know now less interested in becoming teachers and what are the government's solutions to overcome these problems so that in this study the authors used the library research method to conduct research, the results obtained were that the factors that make today's young people less interested in becoming teachers are one of the causal factors namely the low salary of teachers in Indonesia, especially honorary teachers so if we look at it from the welfare side they are still not prosperous, this can be seen from the fact that there are still many honorary teachers in Indonesia who work part-time outside of teaching hours to make ends meet so that this makes young people less interested in becoming teachers because their welfare is not guaranteed so that to overcome this problem the government issued a PPPK policy by opening the formation of around 1 million specifically for students, the purpose of this PPK policy is to make honorary teachers prosperous in Indonesia, but with the existence of this PPK policy it turns out to have positive and negative impacts, the positive impact that gives rise to this policy is that honorary teachers get decent welfare because they no longer have to look for side jobs to meet their needs so that teachers can focus more on their work as educators so that the learning process can be carried out optimally while the negative impact caused by this policy is the negative impact namely the acceptance of government employees with this work agreement. private schools that experience a shortage of teachers because teachers who take part in and pass the PPPK selection are transferred to public schools. So this makes private schools experience a shortage of students. private school principals who pass PPPK will still be assigned to their school of origin.